The Impact of Artificial Intelligence on Education in Indonesia: A Systematic Literature Review of Applications, Challenges, and Future Development Directions - Tarani, Muhammad Natsir; Ali, Mohamad; Wachidi, Wachidi; Mukti, Oscharil Aji (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Artificial Intelligence (AI) has become a transformative force in education globally, including in Indonesia, by offering solutions to improve teaching, learning, and education management. This study aims to provide a comprehensive overview of the application of AI in Indonesian education through the Systematic Literature Review (SLR) approach combined with bibliometric analysis. This study identifies the various applications of AI used in Indonesian education, the challenges faced in their implementation, and the direction of research and policy development that can strengthen the integration of AI in the education sector. Based on an analysis of 74 articles published between 2022 and 2026, key findings show that generative AI, such as ChatGPT, is becoming one of the most widely applied technologies in higher education, particularly in language learning and academic writing. The main challenges faced are infrastructure gaps, the digital readiness of teachers, and policies that are not comprehensive. Future research is suggested to focus on national policy development, practice-based training for teachers, and the development of more adaptive and inclusive AI technologies. This study provides important insights for policymakers and education practitioners in designing more effective AI adoption strategies in Indonesia.